ELECTRICAL PARAMETERS OF THE UPPER CARBON ROCKS (RUNOVSHCHYNSKA AREA OF THE DNIEPER-DONETSK BASIN) - Vyzhva, S.; Onyshchuk, V.; Onyshchuk, I.; Reva, M.; Shabatura, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The main objective of this article is to study electrical parameters of sandstones and argillites of the Upper Carbon rocks in the Runovshchynska area of the Dnieper-Donets basin. It has been determined that specific electrical resistivity of dry rock samples (specific electrical resistivity of rock matrix) varies from 44,802 k Ω·m to 6,115 М Ω·m (average 751,328 k Ω·m). Specific electrical resistivity of sandstones is 3,45 times more than argillitesdue to different shaliness of studied rocks. Specific electrical resistivity of saturated rocks samples varies from 0,54 Ω·m to 10,46 Ω·m (average 1,23 Ω·m). Specific electrical resistivity of argillites is 2,46 times more than sandstones because the latter had high content of reservoir water in their pores (sandstones had better conductivity). It has been determined that formation resistivity factor of sandstones in atmospheric conditions varies from 6,05 to 33,71 (argillites 11,8), and argillites – from 4,76 to 51,47 (average 17,4). Physical modelling of reservoir conditions(temperature t = 78,5 °С, pressure p = 31–31,9 MPa, mineralization M= 170 g/l) showed that specific electrical resistivity varies from 0,3 Ω·m to 3,0 Ω·m (average 0,75 Ω·m). Sandstones in reservoir conditions had the range from 0,3 Ω·m to 2,3 Ω·m (average 0,7 Ω·m), and argillites – from 0,5 Ω·m to 3,0 Ω·m (average 1,2 Ω·m). In this case, specific electrical resistivity of argillites is 1,6 times more than sandstones. Due to the closure of microcracks and the deformation of the pore space, the electrical resistance of rocks increases with increasing pressure. The dependence of formation resistivity enlargement factor on pressure for the studied rocks is expressed by 2-order polynomials. The formation resistivity factor of the studied rocks in reservoir conditions has been determined. It was defined that sandstones in reservoir conditions had the range of the formation resistivity factor from 5,4 to 63,3 (average 20,3), and porosity coefficient – from 0,038 to 0,175 (average 0,113). The range of the formation resistivity factor for argillites was from 13,4 to 88,7 (average 34,3), and porosity coefficient – from 0,043 to 0,115 (average 0,086). Analysis of data of laboratory electrometric investigations has allowed establishing correlations between the porosity coefficient and formation resistivity factor. In addition, the correlation of electrical parameters of rocks in atmospheric and reservoir conditions and the formation resistivity enlargement factor from the water saturation coefficient, taking into account the lithological varieties of the studied rocks, was established.